2008
DOI: 10.1111/j.1553-2712.2008.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation Set Correlates of Anogenital Injury after Sexual Assault

Abstract: Objectives: Forensic investigators remain unsure exactly why some sexual assault victims display acute injury while others do not. This investigation explores potential reasons for these differential findings among female victims.Methods: This cross-sectional analysis examined data from consecutive female sexual assault victims, at least 12 years old, who agreed to a forensic exam between November 1, 2002, and November 30, 2006. Exams utilized colposcopy, anoscopy, macrodigital imaging, and toluidine blue dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…Contrasting the findings of Sachs et al in an estrogenized female population and Drocton et al in an adult population, our data showed increase injury in patients reporting penetrating assault in multiple positions versus the back only position (OR 1.41, 95% CI = 1.05 to 1.91) [3,4]. McLean et al did not find an association for position in their adult population [10].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Contrasting the findings of Sachs et al in an estrogenized female population and Drocton et al in an adult population, our data showed increase injury in patients reporting penetrating assault in multiple positions versus the back only position (OR 1.41, 95% CI = 1.05 to 1.91) [3,4]. McLean et al did not find an association for position in their adult population [10].…”
Section: Discussioncontrasting
confidence: 57%
“…We further explored correlates of AGIs with a logistic regression model choosing independent variables based on prior work and plausible association with injury [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…10 Although visible injury may be present, it is not unusual to have a normal or nonspecific anogenital examination. 41 Injuries that do occur typically heal quickly, within days to a few weeks, and scarring is very unusual. 42 With the patient's assent, a sexual assault evidence kit may be obtained if the assault has occurred within the past 72 hours (up to 96 hours in some jurisdictions).…”
Section: Victim Identification and Evaluationmentioning
confidence: 99%
“…Some reports classified injuries by type and location, 13,14,19,20 whereas others simply noted the presence or absence of genital injury. 15,21 Redness and swelling were not defined as injuries in 2 of the studies because of inconsistent identification, poor inter-rater reliability, and limitations associated with photographing these findings. 19,20 Increased injury frequency was documented in patients reporting virgin status prior to the incident 14,15 and in survivors whose examinations were completed within 24 hours of nonconsensual intercourse.…”
Section: Injuries and Nonconsensual Intercoursementioning
confidence: 99%
“…Only one study specifically documented injury rates for different penetration types. 15 Likewise, no consistent method of injury documentation was used between studies. A commonly used clinical approach to genital injury documentation is the Tears, Ecchymoses, Abrasions, Redness, and Swelling (TEARS) mnemonic.…”
Section: Injuries and Nonconsensual Intercoursementioning
confidence: 99%